2010
DOI: 10.1186/1471-2482-10-28
|View full text |Cite
|
Sign up to set email alerts
|

Saphenofemoral arteriovenous fistula as hemodialysis access

Abstract: BackgroundAn upper limb arteriovenous (AV) fistula is the access of choice for haemodialysis (HD). There have been few reports of saphenofemoral AV fistulas (SFAVF) over the last 10-20 years because of previous suggestions of poor patencies and needling difficulties. Here, we describe our clinical experience with SFAVF.MethodsSFAVFs were evaluated using the following variables: immediate results, early and late complications, intraoperative and postoperative complications (up to day 30), efficiency of the fist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…The largest series of GSV access has reported a 30-day access loss rate of 21 from 56 fistulas (37.5%) with 20 cases as a result of access thrombosis. 2 Pierre-Paul et al reported similar findings with a primary patency of only 7 months and an average of three balloon percutaneous transluminal angioplasties per patient. In addition to two operated pseudoaneurysms, only five of seven fistulas had been successfully used for dialysis, and all patients developed vein loop stenosis.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The largest series of GSV access has reported a 30-day access loss rate of 21 from 56 fistulas (37.5%) with 20 cases as a result of access thrombosis. 2 Pierre-Paul et al reported similar findings with a primary patency of only 7 months and an average of three balloon percutaneous transluminal angioplasties per patient. In addition to two operated pseudoaneurysms, only five of seven fistulas had been successfully used for dialysis, and all patients developed vein loop stenosis.…”
Section: Discussionsupporting
confidence: 60%
“…Few reports exist on the utilization of the great saphenous vein (GSV) for vascular access with poor results. 1,2 Most surgeons today utilize prosthetic grafts or transposition of the femoral vein (tFV) for lower limb access. 3 In this report, we describe an optimized technique for GSV reconstruction in order to serve as a dialysis conduit.…”
mentioning
confidence: 99%
“…At the end of the follow‐up period, the flow rates of all fistulas were measured by Doppler sonography and by its base. They were grouped as good (> 300 mL/min), moderate (100–300 mL/min), and poor (< 100 mL/min) . All patients were dialyzed by their shunts in the follow‐up period by the same dialyzers.…”
Section: Methodsmentioning
confidence: 99%
“…They were grouped as good (> 300 mL/min), moderate (100-300 mL/min), and poor (< 100 mL/min). 8 All patients were dialyzed by their shunts in the follow-up period by the same dialyzers. Number 14 dialysis needle was used for venipuncture and the mean duration of each procedure was 4 hours.…”
Section: Methodsmentioning
confidence: 99%
“…It is created by anastomosis of the distal femoral artery and the great saphenous vein ( Figure 11) which is subcutanously transposed to allow cannulation. Access survival is acceptable [41].…”
Section: Sapheno Femoral Arteriovenous Fistulamentioning
confidence: 99%